The Chinese automobile industry’s research and development capability and innovative performance - Liu, Jili; Liu, Guoxin; Cui, Hainan; Chen, Yuehua (Frontiers in Psychology, 2023)
The Report of China’s Automobile Industry Development 2016 points out that China’s automobile industry faces increasingly fierce competition from global peers, and domestic automobile manufacturers shall continuously improve independent innovation and industry innovative performance. Automobile manufacturers’ participation in distributed innovation and their research & development (R&D) capability play a key role in the growth of innovative performances of China’s automobile industry. With development of China’s automobile industry as the background, this study presents a theoretical framework of correlation of distributed innovation embedment, R&D capability and innovative performances of China’s automobile industry from the microscopic perspective of single industry. Several hypotheses were proposed and then verified by empirical method. Specifically, 117 effective questionnaires were collected and analyzed quantitatively, followed by hypothesis test. The results clarify the working principles of the three dimensions of distributed innovation embedment influencing innovative performances of China’s automobile industry and improvement of R&D capability of enterprises by distributed innovation. This study provides references to improvements of innovative performances of China’s automobile industry.